Alpha diversity of lichenized and aphyllophoroid fungi in two 1ha forest plots in the Samursky National Park (Republic of Dagestan, Russia) - A. B. Ismailov; S. V. Volobuev; Yu. Yu. Ivanushenko (Юг России: экология, развитие, 2024)
Aim. The results of the inventory of species composition of epiphytic lichens and aphyllophoroid fungi on two 1 ha sample plots in lowland floodplain forests are presented. Such integrated studies of these groups of organisms are poorly known. Fungi, including lichenized fungi, are essential components of forest ecosystems. Data on their diversity and substrate distribution can provide important information on the condition and biological value of the forests studied.   Material and Methods. The main method of the fieldwork was the "1‐ha method". For the alpha‐diversity study, two 1‐ha sample plots were established in well‐preserved forest areas: the first one in a site of mixed broad‐leaved forest with lianas, and the second one in communities dominated by Carpinus betulus and Quercus robur. The specimens were collected from all variety of woody substrate within plots in spring and autumn 2023.   Results. We have revealed 89 species of lichens and 60 species of aphyllophoroid fungi. The lichen families Arthoniaceae, Lecanoraceae, Physciaceae, Ramalinaceae and Roccellaceae contain 47.2 % of all species. High proportion of lichens with Trentepohlia photobiont (29.2 %), significant number of Arthoniomycetes (Arthoniaceae, Lecanographaceae, Roccellaceae) and crustose lichens (75.3 %) have been noted. Among the aphyllophoroid fungi identified in the sample plots, 11 species are new to Dagestan, including three species (Antrodia leucaena, Coronicium gemmiferum, Steccherinum litschaueri) recorded for the Caucasus for the first time. Fourteen species are new to the Samursky National Park.   Conclusion. The study of alpha diversity and substrate preferences of xylobionts revealed the richest and most specific phorophytes, as well as some ecological features of the surveyed plots. Most of the species were found on the bark and wood of Carpinus betulus, Populus alba and Quercus robur. The majority of species reported for the first time for the region have been recorded on these tree species. We expand the number of known species on Populus alba, on which only few species were previously known. High proportion of lichens with the Trentepohlia photobiont and the predominance of crustose species were revealed. In terms of basidiomata morphology, corticioid fungi dominated over polypores and clavarioids in general. The leading ecological and trophic group of aphyllophoroid fungi are saprotrophs. Revealed features indicate a significant contribution of the wood of the main forest‐forming tree species to the preservation of the species richness of myco ‐and lichen biota.